Measuring the Service Quality of Public Libraries in Ankara - Özlem Şenyurt Topçu; Bülent Yılmaz (Türk Kütüphaneciliği)
Measuring the service quality in corporations periodically is one of the basic components of service policies. Measuring service quality is a required action in order to develop the services and compare them with the ones in similar corporations. The purpose of this study is to evaluate the service quality of the specific public libraries in Ankara on a scale base. The libraries included in this research are Cebeci Public Library (Cebeci HK), Mamak County Public Library (Mamak İHK) and Or-An Sevgi Yılı Public Library (Or-An HK) which are chosen from the upper, middle and lower socio-economic regions in Ankara. Within the frame of the research, a survey basing on Libqual+™ Service Quality Scale is conducted to 120 users from these three libraries. According to the findings of the research, the users are generally satisfied with the service quality of these libraries.However, they have some displeasure in terms of access to information and public relations in those libraries. The users give 7.2 points over 9 for the entire service quality components of these libraries and for this issue there is no significant difference among the libraries.